ANALISIS PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEMERINTAH DAERAH KOTA MALANG - Suprianti, Martina Merliana; wulandari, Retno; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2020)
This research aims to explain and describe the influence of budgeting participation, clarity of objectives, and organizational commitment to employee performance. This study uses a quantitative approach method, with a total sample of 70 employees in 14 OPD City Malang. Measuring tool using a Likert scale with a score of up to 5 items. Using multiple linear regression analysis and to test the level of significance using the f test and hypothesis testing using the t test with the help of the SPSS 22 program. Partially addressed that budgeting participation has a significant effect on the performance of the city government of Malang, the clarity of the target has a positive effect on the performance of the city government of Malang , and organizational commitment does not affect the performance of the city government of Malang, as well as the simultaneous results that the participation of budgeting, clarity of objectives and organizational commitment affect the performance of the city government of Malang.